The Effect of COVID-19 Lockdown on Oral Glucose Challenge Tests and Body Mass Indexes in Türk Pregnant Women - Akdas Reis, Yildiz; Firatligil, Fahri Burcin; Akay, Arife; Kalayci Oncu, Asya; Engin Ustun, Yaprak (Gynecology Obstetrics & Reproductive Medicine, 2022)
OBJECTIVE: To investigate the glycemic status of pregnant women by the comparison of 50 g glucose challenge test results and body mass index changes in the pandemic period versus last year’s test results. STUDY DESIGN: In this case-control study two groups were constituted. Group 1 included patients who underwent a glucose challenge test in the year 2019 before the pandemic lockdown (n=604) was assessed as the control group; group 2 (n=505) included patients who underwent the same test in the year 2020 that in the pandemic lockdown period was evaluated as the study group. RESULTS: Pandemic lockdown affected the gaining weight in every level of educational status who did not exercise, but there was only a statistical difference between university-educated participants. We could not see any negative effect of the pandemic lockdown on glucose challenge test results. But only in the university-educated participants, there was an effect on increased glucose challenge test levels. CONCLUSION: Our study and the other studies designed like ours show that the pandemic lockdown affects our life worse.